Differences in Mental Health among Migrants and Non-migrants in South Africa: Evidence from the National Income Dynamics Study - Govera, Hemish (African Human Mobility Review, 2021)
The literature associates migration with poor mental health outcomes. Despite extensive empirical research in other countries, there is a paucity of research examining the mental health consequences of migration in South Africa, and the factors that compound the relationship between the two variables. The study objective was to evaluate the differences in the mental health status of internal migrants and that of non-migrants in South Africa with a special focus on depressive symptoms. The study considered the influence of various vulnerability and sociodemographic factors such as gender, age, educational attainment, race, income group, marital status and province of residence. Mental health disorders are already considered the largest contributor to the global disease burden. Hence, understanding the nature of the relationship between migration and mental health is critical for public health prevention efforts. To make the determination, the study applied descriptive analysis and logistic modelling based on the South African National Income Dynamics Study (NIDS) panel datasets of 2008, 2010, 2014/15 and 2017. Descriptive statistics were employed to derive the frequency distribution of sociodemographic characteristics and migration factors. Logistic regression analysis was used to assess the associations between depression, migration and sociodemographic factors.